Assessing the Knowledge of Students about Dental Bleaching in Shahid Bahonar University of Kerman, Iran - Marzieh Karimi-Afshar; Ali Eskandarizadeh; Molouk Torabi-Parizi; Reyhaneh Aftabi (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: An attractive smile and white teeth give self-confidence and provide impression of health, which help individuals for social and interpersonal success. Increasing demand for tooth bleaching and lack of relevant information on the other hand, necessitate a new investigation to assess the knowledge of the students about dental bleaching in Kerman. Purpose: This study was designed to assess the overall knowledge of the students of Shahid Bahonar University of Kerman regarding dental bleaching and their tendency to perform it. Materials and Method: This cross-sectional study enrolled 384 students who were selected by simple random sampling. A valid and reliable self-administered researcher-made questionnaire was employed to collect data about demographic information, health behavior, tooth bleaching, and the tendency to perform .This tool contained 8 questions with the focus on the knowledge of dental bleaching. Data were analyzed by using SPSS version 21 and regression analysis at a significant level of 0.05. Results: Overall, 59.55% of participants were male and 40.45% were female students. Most likely, the source for gaining information was internet. In this regard, 29 individuals were dissatisfied with tooth color, 27 ones with the appearance of teeth, 13.5% have done tooth bleaching, and 69% had tendency to do that. The preferred knowledge was about the difference between scaling and root planning (SRP) and bleaching. There was no significant difference between age, gender, and marital status variables with the knowledge of dental bleaching. Tooth color satisfaction increased the tendency to do bleaching about 1.87 times. Conclusion: The study highlights that 69 % of the students had a tendency to do the bleaching, their knowledge was moderate, and there was no statistical relationship between knowledge, gender, and marital variables. Color variable had an overall positive effect on the tendency to do the bleaching.